The Social Construction of the Banjar Ethnic Society Toward the Radap Rahayu Dance - Nugraheni, Edlin Yanuar; Artaria, Myrtati Dyah; Sutinah, Sutinah; Bull, Ronald Lukens (Jurnal Ilmiah Peuradeun, 2024)
The Radap Rahayu is a ritual dance performed today by the Banjar ethnic group in Gambut District, Banjar Regency, South Kalimantan. It is used for traditional Banjar rituals, such as weddings, bathing, and building erections. This research aimed to describe the importance of the Radap Rahayu dance for the Banjar people and its relation to their well-being and spirituality. This qualitative research used a theoretical framework established by Berger and Luckmann (1990). Through the social construction theory, the researchers explored how the Banjar people make sense of their culture and express their spirituality through art. The informants were determined using purposive sampling on 25 individuals, and data collection was conducted through observations and in-depth interviews. The data was analyzed using thematic analysis and reviewed based on existing literature. The findings showed that the function and meaning of the Radap Rahayu dance, according to the Banjar people, are not merely an art performance but a vital ritual integrated into their daily lives. The researchers identified limbai movement, spiritual meaning, spiritual beings, and guardian crocodiles as domains of social construction. This aligns with the framework, highlighting that a phenomenon displays multiple realities.